PENGARUH BIMBINGAN ORANG TUA TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 PALENGAAN PAMEKASAN TAHUN PELAJARAN 2022-2023 - Fitriyah, Dianatul; Kulsum, Ummu (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
The higher the parent's education level, the higher their role in the family's (children's) education. Thus, the influence of parental education level on student learning achievement at SMP Negeri 2 Palengaan Pamekasan is interesting to study and research. The approach used in this research is quantitative with technical product moment formula analysis. The number of samples used was 50 students. The research results can state that there is an influence of parental guidance on students' learning achievement in Islamic religious education subjects at SMP Negeri 2 Palengaan Pamekasan for the 2022-2023 academic year. which can be concluded from the results of data analysis which obtained a figure of 0.68 from 50 samples. These results were compared with the "r" product moment table both at a significance level of 5% and at a significance level of 1%, where at df=N-nr=50-2=48 the values ​​obtained were 0.320 and 0.510. Parental guidance has quite an influence on students' learning achievement in Islamic religious education subjects at SMP Negeri 2 Palengaan Pamekasan for the 2022-2023 academic year. This is proven that the work "r" of 0.68 is in the range of 0.40-0.70 with a fair or moderate interpretation. The implications of this research are: 1) A more active role for parents, 2) Development of a Parent Guidance Program, 3) Collaboration between Schools and Parents, 4) Development of Parent Guidance Materials, 5) Development of Resources for Parents.